Analysis of oil palm plantation performance in environmental management based on ISPO principles and criteria. Issue 1 (March 2021) - Nasution, A R Habibi; Hariyadi,; Kartodiharjo, H
Abstract: Excellence, potential, and good prospects make palm oil plantations grow rapidly. Another underlying consideration is the important and strategic role as a activator nor accelerator in development and economy. Environmental and social issues become challenging in development's sector, especially in the development of sustainable oil palm plantations. Since the implementations of the certification system for sustainable palm oil plantation's in 2011 and was further clarified in Regulation of the Minister of Agriculture No. 11 of 2015 about Indonesian Sustainable Palm Oil Certification System (ISPO), the Indonesian Government requires companies to produce palm oil sustainably. This research aims to analysis on the performance of oil palm plantations in environmental management based on ISPO principles and criteria. Research on several palm oil plantations of South Sumetera Province located in Musi Banyuasin Regency. Methods were used by collecting primary data through interviews and secondary data was obtained from data reviews such as company literature. The results of the analysis showed that the effectiveness of policy implementation through the fulfillment of environmental policy components can be fulfilled by most of companies. Meanwhile, in some cases, such as online reporting of land fires has not been fulfilled yet.